A Case Report of Mycoplasma hominis Subdural Empyema Following Decompressive Craniotomy, and a Review of Central Nervous System Mycoplasma hominis Infections - Potruch, Assaf; Rosenthal, Guy; Michael-Gayego, Ayelet; Temper, Violeta; Abdelrahman, Mohanad; Ayalon, Oshrat; Nir-Paz, Ran; Oster, Yonatan (Frontiers in Medicine, 2022)
Background Mycoplasma hominis is a small cell-wall-free organism, part of the normal microbiota of the genitourinary tract. It is rarely involved in extragenital infections, mainly joint, surgical-site, and respiratory infections. Methods We describe a case of M. hominis subdural empyema and lower limb surgical site infections, following decompressive craniotomy, after traumatic brain and extremities injury. In addition, a literature review of 34 cases M. hominis CNS infections was done. Results Our case depicts a 25-years old patient who developed subdural empyema and surgical site infections in his cranium and fibula. Both sites were cultured, and small pinpoint colonies grew on blood agar. MALDI-TOF MS identified M. hominis. Simultaneously 16S-rDNA PCR from CSF detected M. hominis. Antimicrobial treatment was switched to doxycycline with improvement. Literature review revealed 21 adults and 13 pediatric cases of M. hominis CNS infection. Risk factors in adults were head trauma, neurosurgery, or post-partum period. Conclusions Based upon the literature reviewed, we postulate that adult patients with head trauma or neurosurgical procedure, rarely are infected either through direct contamination during the trauma, or by undergoing urgent, urinary catheterization, and may experience distant infection due to translocation of M. hominis into the bloodstream. In such cases diagnosis is delayed due to difficulties in growing and identifying the bacteria. Empiric antimicrobials are usually not effective against mycoplasmas. These factors contributed to the mortality in adult cases (15%). Our rare case highlights the necessity of combining classical microbiology routines with advanced molecular techniques to establish a diagnosis in complicated cases.